Wade in the Water Children: Charles Long, Karl Barth, and the (Re)Imagination of Matter - Vadear en el Agua, Niños: Charles Long, Karl Barth y la (Re)Imaginación de la Materia - Carr, Raymond (2021)
[When the Swiss theologian Karl Barth visited America in 1962, he had a private conversation with Charles H. Long, who asked, among other things, "How do you like this strange place called the United States?" The locus for Long's question—the black religious experience—complicated Barth's audacious proposal that American theologians should develop a theology of freedom. Long's question, furthermore, outflanked Barth by calling for the recognition of America as a hermeneutical situation and advancing the (de) constructive argument that "a theology of freedom is first a destruction of theology as a powerful mode of discourse." This article suggests that the way toward Barth's so-called theology of freedom is to develop theology in this (de)constructive mode by recharting the Mediterranean and Atlantic worlds in order to catalyze the (re)imagination of matter. Such recasting of our thought means "going back into the water," specifically the Pacific Ocean, for a reorientation. Cuando el teólogo suizo Karl Barth visitó los Estados Unidos en 1962, tuvo una conversación en privado con Charles H. Long, quien le preguntó, entre otras cosas, "¿Qué tal te parece este extraño lugar llamado Estados Unidos?" El lugar para la pregunta de Long—la experiencia negra religiosa—complicó la audaz propuesta de Barth de que los teólogos norteamericanos deberían desarrollar una teología de liberación. La pregunta de Long, además, superó a Barth al exigir el reconocimiento de los Estados Unidos como una situación hermenéutica y al promover el argumento (de)constructivo de que "una teología de liberación es primeramente una destrucción de la teología como un potente modo discursivo." Este ensayo sugiere que el rumbo hacia la tal llamada teología de liberación de Barth es desarrollar la teología en este modo (de)constructivo al renovar los mundos mediterráneo y atlántico para catalizar la (re)imaginación de la materia. Tal reestructuración de nuestro pensamiento significa "volver al agua," específicamente al Océano Pacífico, para reorientarnos.]